Friendship among nations : history of a concept - Roshchin, E. (Evgeniĭ), 1979- (Manchester International Relations, 2017)
This is a study of friendship in international politics. It offers the history of friendship, and shows the role of friendship in building various legal and political orders on both equal and unequal terms. Told through an examination of sources ranging from diplomatic letters and bilateral treaties to poems and philosophical treatises.